THE INFLUENCE OF INFANT FEEDING PRACTICES AND PARENT ATTACHMENT ON NUTRIONAL STATUS OF UNDES FIVE CHILDREN IN DESA GUNUNG MADDAH SAMPANG - Eny Susanti (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2020)
Nutrional status is one of factors that determine human resource and the quality of life. At the matter of the fact, we still pad nutrition was found on under five children. The goal of this research is analyze the influence of infat feeding practices and parent attachment on nutrional status of under five children in Desa Gunung Maddah Sampang. Analitic Design and the present cross sectional method was conducted on this study. We selected 129 undre five children in Desa Gunung Maddah on June 2015, and 98 as sample. Random sampling technique was used to select under five children as study object. Questioner and KMS were used for data collection, KMS consist of nutritional status weight for age by using spearman statistic.Spearman rho analysis shawed that there were the impact of infant feeding practices correlation coefficient=0,810 (p=0,000) and also parent attachment impact on nutritional status of under five children correlation coefficient=0,579 (p=0,000). Based on this research, we have to prevent significant risk factors for under nutritition among under fives. That’s way midwives have to give them lots of informations about how important ASI is also care of infant feeding practices in order to there won’t be significant risk factors happened.